ANTIBACTERIAL POTENTIAL OF ESSENTIAL OILS DERIVED FROM NATURAL, CALLUS AND IN-VITRO PROPAGATED SOURCES OF MELALEUCA ALTERNIFOLIA AGAINST COMMON BACTERIAL PATHOGENS - M., JEYAKANI; A., KUMARI NIRMALA; M., RAJALAKSHMI (International Journal of Current Pharmaceutical Research, 2021)
Objective: Melaleuca alternifolia (M. alternifolia) and its essential oil (EO) fractions have been used widely and traditionally in the treatment of various infectious diseases and hence its antibacterial potential is investigated in the present study. Methods: The antibacterial activity was studied through the agar disc diffusion method and broth dilution method, DNA fragmentation studies and confocal microscopy morphological studies were done. In-silico molecular interaction was studied against microbial target using docking software. Results: The inhibitory concentration of the EOs was recorded at 75% dilution with larger inhibition zones. The DNA fragmentation analyzed in the essential oil derived from in-vitro propagated leaves (EOIPL) of M. alternifolia treated bacterial cultures was compared with negative and positive controls. In Minimum Inhibitory Concentration (MIC) of EOIPL treated Staphylococcus aureus (S. aureus) showed time-dependent growth inhibition. The DNA content in the EOIPL treated bacterial cultures was comparatively less than in control cultures. The cell morphology changes of S. aureus cells were studied through confocal laser scanning microscopic analysis which showed a significant decrease in viable bacterial cells. The active component, terpinen-4-ol docked to autolysin receptor revealed stable interaction with the microbial target. Conclusion: Thus EOIPL was explored to possess bactericidal activity against common infectious bacteria and could in incorporated in therapeutic natural antibiotic formulations as with future studies.